2021
DOI: 10.1186/s12862-021-01938-y
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of ecotypes in a parasitoid wasp: a case of incipient sympatric speciation in Hymenoptera?

Abstract: Background To understand which reproductive barriers initiate speciation is a major question in evolutionary research. Despite their high species numbers and specific biology, there are only few studies on speciation in Hymenoptera. This study aims to identify very early reproductive barriers in a local, sympatric population of Nasonia vitripennis (Walker 1836), a hymenopterous parasitoid of fly pupae. We studied ecological barriers, sexual barriers, and the reduction in F1-female offspring as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 153 publications
(170 reference statements)
1
10
0
Order By: Relevance
“…Our results indicate that sexual isolation, albeit weak and unilateral, emerges as first barrier between closely related strains without obvious ecological separation, such as the use of different hosts, and increases in strength during the process of separation. This agrees with other data on reproductive barriers in L. distinguendus (König, Zundel, et al, 2019), and with the recent study on reproductive barriers within a population of N. vitripennis (Malec et al, 2021), where slight sexual isolation was found between closely related populations and even within a population of the same species. As in N. vitripennis, sexual isolation in L. distinguendus is most likely caused by a mate choice decision of the female, which do not accept males with diverging mandibular pheromones that are applied on the female antennae during courtship (König, Seeger, et al, 2015;Ruther & Hammerl, 2014).…”
Section: Sexual Isolationsupporting
confidence: 93%
“…Our results indicate that sexual isolation, albeit weak and unilateral, emerges as first barrier between closely related strains without obvious ecological separation, such as the use of different hosts, and increases in strength during the process of separation. This agrees with other data on reproductive barriers in L. distinguendus (König, Zundel, et al, 2019), and with the recent study on reproductive barriers within a population of N. vitripennis (Malec et al, 2021), where slight sexual isolation was found between closely related populations and even within a population of the same species. As in N. vitripennis, sexual isolation in L. distinguendus is most likely caused by a mate choice decision of the female, which do not accept males with diverging mandibular pheromones that are applied on the female antennae during courtship (König, Seeger, et al, 2015;Ruther & Hammerl, 2014).…”
Section: Sexual Isolationsupporting
confidence: 93%
“…Due to the long-standing postulation of the discernibility between the bird and carrion ecotypes of N. vitripennis (Grassberger and Frank, 2004;Peters and Abraham, 2010;Malec et al, 2021), our findings that clearly do not support their unambiguous differentiation on a phenotypic and genetic level were unexpected. An important aspect largely neglected in earlier studies conducted on populations of this species is the estimation of how frequent habitat switches can occur in nature.…”
Section: Discussionmentioning
confidence: 64%
“…A recent study demonstrated very early reproductive barriers between the nest and carrion ecotypes in a sympatric N. vitripennis population from Southern Germany, hinting at premating and sexual isolation preceding ecological separation (Malec et al, 2021). Here, we focus on a sympatric N. vitripennis population from the Netherlands and test for potential degrees of separation between the different ecotypes on a phenotypic and population genetic level.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nicholls et al., 2010). Conversely, chalcid wasps can undergo rapid speciation by the emergence of ecotypes (Malec et al., 2021) or cytoplasmic incompatibility (Gebiola et al., 2016) and thus may be prone to sympatric speciation (König et al., 2019). Logically, the range of a parasitoid species will be limited by the range of its host(s).…”
Section: Discussionmentioning
confidence: 99%